The Role of Communication in Improving Community Health Through Quality Service - Banda Napitupulu; Lucytha Carolina; Lody Winata; Fika Fibryanita; Marhaeni Fajar Kurniawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Public health is a pillar of the development of a nation. Health is one of the basic human needs. The process of service to the public requires good communication between the government as the party providing services and the community as the party being served, the formation of good communication will not only give satisfaction to the public but will also lead to the efficiency of services carried out by the government. This study aims to find out how the role of communication in improving the health status of the community through quality services and what obstacles are faced by the government in improving the health status of the community through quality services. This study uses a literature review research method with a descriptive approach obtained from indexed electronics based such as Google Scholar, and other database sources equipped with DOI. The results of the study are presented in the form of a descriptive narrative. According to Carl I. Hoveland in Mulyana (2005:62) that communication is a process that allows a person (the communicator) to convey stimuli to change the behavior of others. The concept of public service is derived from the meaning of public service, which means: "a variety of activities aimed at meeting the needs of the community for goods and services". Public service communication itself is a communicator who acts as a sender of messages in a communication process. In public service communication, there are people who play a role in conveying messages, called communicators. A public service communicator is a person or group of people from the public bureaucracy who send/deliver news/messages and provide services (serve) the needs of people or society as citizens.